Impact of a pharmacist-driven antimicrobial stewardship program in a private hospital in Costa Rica - José Pablo Díaz-Madriz; Eugenia Cordero-García; José Miguel Chaverri-Fernández; Esteban Zavaleta-Monestel; Josué Murillo-Cubero; Hellen Piedra-Navarro; Marian Hernández-Guillén; Tiffany Jiménez-Méndez (Pan American Health Organization, 2020)
Objective. To measure the impact generated by the implementation of the pharmacy-driven antimicrobial stewardship program of the Clínica Bíblica Hospital. Methods. This is a retrospective observational study that evaluates the consumption of antibiotics for the periods before and during implementation of the Clínica Bíblica Hospital antimicrobial stewardship program, calculated by means of defined daily dose per 1 000 patient-days and days of therapy per 1 000 patient-days. In addition, bacterial resistance patterns for the periods 2014-2015 and 2016-2017 were compared. Results. Consumption of most-used antibiotics was calculated, looking for trends that might be associated with the activities implemented by the Clínica Bíblica Hospital antimicrobial stewardship program. Comparing some of the antibiotics with the highest consumption in periods I and II, use of levofloxacin and ceftriaxone showed a decrease of 54.0% (p < 0.001) and 14.6% (p = 0.003), respectively, whereas there was an increase in the use of cefazolin of 4 539.3% (p < 0.001). Regarding percentage of bacterial resistance, in most bacterial isolates no statistically significant changes were observed between the two periods. Conclusions. A reduction in the overall consumption of antibiotics has been achieved over time, most likely attributable to the antimicrobial stewardship program. However, this trend was not observed for all the antibiotics studied. The pattern of resistance among the commonly isolated microorganisms did not vary greatly between the periods studied, which suggests that either the antimicrobial stewardship program may have prevented an increase in bacterial resistance since its implementation, or that it is too soon to see impact on bacterial resistance.